EFEKTIVITAS MEDIA POWERPOINT INTERAKTIF BERBASIS CANVA PADA PEMBELAJARAN PENDIDIKAN PANCASILA ELEMEN KEBHINEKAAN DI KELAS IV SEKOLAH DASAR KOTA PADANG - Putri Fauziah, Anestra; Reinita; Wahyuni, Etri; Anita, Yesi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
his study aims to analyze the effectiveness of interactive PowerPoint media based on Canva in Pancasila Education learning on the diversity (Bhinneka Tunggal Ika) element for fourth-grade elementary school students in Padang City. The research employed a Research and Development method using the ADDIE model, which encompasses five stages: analysis, design, development, implementation, and evaluation. The research subjects were students of SDN 13 Kapalo Koto, SDN 02 Cupak Tangah, and SDN 20 Binuang Kampung Dalam. Effectiveness was measured through pretest and posttest instruments using N-Gain score analysis. The findings indicated that: (1) SDN 13 Kapalo Koto achieved an average pretest score of 68 and posttest score of 89.6, yielding an N-Gain of 0.675, corresponding to an effectiveness percentage of 67.5% (effective category); (2) SDN 02 Cupak Tangah achieved an average pretest of 63.2 and posttest of 86.8, with N-Gain 0.64, corresponding to 64% (effective category); (3) SDN 20 Binuang Kampung Dalam achieved an average pretest of 64.09 and posttest of 87.73, with N-Gain 0.66, corresponding to 66% (effective category). These findings demonstrate that interactive PowerPoint media based on Canva is effective in improving student learning outcomes in Pancasila Education, particularly on the diversity element, in fourth-grade elementary school.